2019
DOI: 10.22237/jotm/1572566580
|View full text |Cite
|
Sign up to set email alerts
|

The tumultuous world of global maritime transportation: a cautionary tale for supply chain managers

Abstract: The past five years have seen unprecedented changes transform the way goods are moved around the world. The expanded Panama Canal now permits larger vessels as well as simultaneous transits in each direction. Coincidently, steamship lines began purchasing a new generation of bigger ships, forcing ports in the United States to make very large investments in new infrastructure. When examined within the context of other environmental events impacting global trade, the total effect has been to put the maritime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…ISSN 1900-6586 (print), 2500-7645 (online) Nevertheless, it should be observed that Gourdin (2019) argued that since economic benefits take too long to become tangible, they are commonly inflated to justify the construction of new waterways, ports, and bridges; however, those economic investments are eventually discovered to be avoidable. Notably, container ports can experience uncertainty because of the unsecured returns of economic investments, the reality of local institutions, the legal framework, the fragmented interdependency of various international logistical actors, the state of the relationship with port workers, and the political and community support for infrastructure projects (Danyluk, 2019).…”
mentioning
confidence: 99%
“…ISSN 1900-6586 (print), 2500-7645 (online) Nevertheless, it should be observed that Gourdin (2019) argued that since economic benefits take too long to become tangible, they are commonly inflated to justify the construction of new waterways, ports, and bridges; however, those economic investments are eventually discovered to be avoidable. Notably, container ports can experience uncertainty because of the unsecured returns of economic investments, the reality of local institutions, the legal framework, the fragmented interdependency of various international logistical actors, the state of the relationship with port workers, and the political and community support for infrastructure projects (Danyluk, 2019).…”
mentioning
confidence: 99%